Сетевое сообщество как инструмент методической поддержки в работе учителя - Тимошенко, Л.И. (My University, 2016)
Relevance. To improve, share and learn from the experience and knowledge of each other it is necessary to create a collaborative learning of teachers. Network communities or teachers' unions - are a new form of organization of professional activities on the network. This is a group of professionals, working in the same subject or problem of professional activity on the network. Participation in professional network associations allows teachers, living in different parts of the same country and abroad, to communicate with each other, to solve professional problems, to realize themselves and improve their skills. Goal. Creation of innovative model of professional development. Methods.Methods. Conversation and analysis of necessity of the creation and development of professional network community for information and methodological support of teachers, improvement of their skills. Result. • Creation of a single information space; • Exchange of experience, support and cooperation; • Dissemination of successful teaching practices; • Organization of formal and informal communication on professional topics; • Initiation of virtual collaboration for the following interaction outside of Internet; professional development; • Support for new education initiatives. Conclusion. Creation of the professional networking community will expand opportunities to create collaborative learning environment of teachers and will improve the quality of education in the school.
Keywords: continuous vocational training; network community; informational competences; integration into pedagogical community of the Republic of Kazakhstan.; creative self-realization